2016
DOI: 10.1093/intqhc/mzw076
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary initiative to standardize intensive care to acute care transitions

Abstract: Prior work has shown that structuring handoffs can improve patient safety, but the novelty of this project was addressing the transfer process in its entirety, across silos of care. Factors leading to the success of this project were the involvement of key stakeholders across the entire institution early in the project development phase, employment of lean methodology, and implementation of tools to guide workflow adherence and track causes of deviation from the workflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…These communication problems are more common in the transition hand-off between two places when the responsibility of the patient shifts between the members of the care team [ 36 ] and if the communication method is not clear and consistent. A basic analysis of these failures showed that the lack of a standard protocol for transition from the ICU to a ward is a contributing factor to the potential risks of harm to the patient [ 37 ]. In this study, the findings indicate that ineffective communication is one of the challenges of the patient transition process from the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…These communication problems are more common in the transition hand-off between two places when the responsibility of the patient shifts between the members of the care team [ 36 ] and if the communication method is not clear and consistent. A basic analysis of these failures showed that the lack of a standard protocol for transition from the ICU to a ward is a contributing factor to the potential risks of harm to the patient [ 37 ]. In this study, the findings indicate that ineffective communication is one of the challenges of the patient transition process from the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Early involvement of stakeholders is important (Halvorson et al, 2016;Parenmark et al, 2019) and involving families of patients can be one way of managing the consensus of diverse stakeholder groups when prioritizing quality improvement suggestions. In a study by McKenzie et al (2017), nine individuals were selected, representing providers, decision makers and patients' families from ICUs within a single geographically defined healthcare system, forming a panel for assessing and reconciling priorities for improving the care of critically ill patients.…”
Section: Resultsmentioning
confidence: 99%
“…Standardizing the patient transfer process is often discussed as a way of improving the patient transfer process (Alali et al, 2019;Halvorson et al, 2016). Lee et al (2019) presented a Improving ICU transitional care queuing network model to study patient transitions.…”
Section: Resultsmentioning
confidence: 99%
“…While it is critical to understand the risks posed to patients during transfers, the impact of transfers on hospital staff from a wide array of professional backgrounds is less well-understood (Halvorson et al, 2016;Rosenberg et al, 2018). Research that acknowledges staff experiences in maintaining patient safety during intra-hospital transfers is needed to understand other factors that contribute to adverse events, delays in care and other risks to patients (Hearld, Alexander, Fraser, & Jiang, 2008).…”
Section: Introductionmentioning
confidence: 99%